Večkodnost v žanrski analizi literarnega branja: Branislava Vičar, Katja Plemenitaš (Stanje in perspektive uporabe govornih virov v raziskavah govora, 2024)
Multimodality in the Genre Analysis of Literary Reading. The article examines the interaction of different semiotic modes in literary reading. The genre of literary reading is characterized by the performance of a literary work. This type of live performance art involves a direct relationship between the interpreters, who can be authors themselves, and the audience. The study of an excerpt from the literary reading of lesbian literature called The Great Lesbian Reading shows the interaction of different semiotic modes and the contextualization of reading aloud by nonverbal modes, such as music, handling an object, body posture, gaze, facial expressions, gestures, etc. The literary reading consists of three consecutive social actions corresponding to the elements of its genre structure: the introduction or announcement, the reading itself (key structural unit), and the coda, i.e., evaluation. A multimodal interaction analysis reveals that the concept of mode as a register variable needs to be expanded to include nonverbal modes.